El derecho a la educación de las personas migrantes y refugiadas / The right to education of migrants and refugees - Muñoz Villalobos, Vernor (Journal of Supranational Policies of Education (JOSPOE), 2016)
ABSTRACT The focus of this report is on those who have crossed national borders, who generally are at risk of marginalization and specifically to discrimination in the provision of education. The research addresses six core issues, the consideration of which follows an analysis of the contextual background. Attention to these issues is viewed as indispensable in meeting the educational challenges and opportunities related to migration. These core, but inevitably interrelated themes are: the legal and normative framework; social and cultural issues; language and curriculum; teachers; accreditation and life long learning. The preparation of the report has benefitted greatly from the active and constructive engagement of many relevant actors including Governments, international organizations, academics, nongovernmental organizations and concerned individuals. Together they have offered a wealth of different perspectives and which form the basis of a number of recommendations ending the text. Keywords: Education, Migration, Curriculum, Accreditation, Human Rights RESUMEN El objetivo de este artículo es sobre las personas que han cruzado las fronteras nacionales, quienes generalmente se encuentran en riesgo de exclusión social y se enfrentan a la discriminación en el acceso y las oportunidades educativas. El texto aborda seis temas principales, seguido de un análisis del marco contextual. La atención a estas cuestiones es indispensable para enfrentar los desafíos y las oportunidades educativas relacionadas con la migración. Los temas tratados están inevitablemente interrelacionados son el marco legal y normativo, las cuestiones sociales y culturales, el lenguaje y el currículo, los maestros, acreditación y el aprendizaje a lo largo de la vida. La elaboración de la investigación que nutre este artículo se ha beneficiado en gran medida de la participación activa y constructiva de muchas partes interesadas, incluidos los gobiernos, organizaciones internacionales, académicos, organizaciones no gubernamentales y personas interesadas. Juntos han ofrecido una gran cantidad de diferentes perspectivas y que forman la base de una serie de recomendaciones con las que termina el texto. Palabras clave: Educación, Migración, Currículo, Acreditación, Derechos Humanos